2018
DOI: 10.1186/s12935-018-0697-6
|View full text |Cite
|
Sign up to set email alerts
|

S-Adenosylmethionine regulates apoptosis and autophagy in MCF-7 breast cancer cells through the modulation of specific microRNAs

Abstract: BackgroundTo get insight into the molecular mechanisms underlying the anti-tumor activity of S-adenosyl-l-methionine (AdoMet), we analyzed AdoMet-induced modulation of microRNAs (miRNAs) expression profile in MCF-7 breast cell line and its correlation with cancer-related biological pathways.MethodsMiRNA expression profiling was performed using a TaqMan MiRNA Array, following 500 µM AdoMet-treatment. The results were confirmed by Quantitative real-time PCR analysis. MCF-7 were transfected with miR-34a, miR-34c … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 67 publications
(74 reference statements)
2
44
0
Order By: Relevance
“…MiRNA-34c and miRNA-449a, that belong to miRNA-34/449 superfamily, share several target genes and a very similar seed sequence, a conserved heptameric sequence comprising nucleotides 2–7 at the 5′ end of the miRNA, essential for binding to target mRNA [ 44 , 45 , 46 , 47 ]. MiRNA-34c and miRNA-449a are downregulated in a wide range of cancers, including human breast cancer suggesting their function as potential tumor suppressors [ 43 , 44 , 45 , 46 , 47 ]. Notably, the up-regulation of miRNA-34 and miRNA-449 has been demonstrated to regulate oncogenic pathways including cell proliferation, metastases and apoptotic pathways [ 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…MiRNA-34c and miRNA-449a, that belong to miRNA-34/449 superfamily, share several target genes and a very similar seed sequence, a conserved heptameric sequence comprising nucleotides 2–7 at the 5′ end of the miRNA, essential for binding to target mRNA [ 44 , 45 , 46 , 47 ]. MiRNA-34c and miRNA-449a are downregulated in a wide range of cancers, including human breast cancer suggesting their function as potential tumor suppressors [ 43 , 44 , 45 , 46 , 47 ]. Notably, the up-regulation of miRNA-34 and miRNA-449 has been demonstrated to regulate oncogenic pathways including cell proliferation, metastases and apoptotic pathways [ 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our research group has thoroughly investigated the antiproliferative and proapoptotic role exerted by AdoMet in breast cancer [ 24 , 41 , 42 ] and recently provided the first evidence that in hormone-positive breast cancer cells AdoMet is able to regulate the expression of miRNA-34a, miRNA-34c, and miRNA-486-5p which play a crucial role in the development and maintenance of the tumor cell phenotype [ 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bioinformatic analysis revealed that LINC02418 and 3'UTR region of BCL2 contained complementary sequence of miR-34b-5p, implying miR-34b-5p could bind to LINC02418 and BCL2 gene. MiR-34b-5p belongs to the miR-34 family which has been reported to be tumor suppressor and therapeutic candidate in cancer [33][34][35][36]. Dual-luciferase activity assays con rmed the interaction between miR-34b-5p and LINC02418 (Fig.…”
Section: Discussionmentioning
confidence: 94%
“…In a recent work, it was demonstrated that, in hepatocellular carcinoma, the reduction in the expression of methionine adenosyltransferase genes, coding the enzyme that synthesizes AdoMet can be attributed to the regulation of miRNAs, resulting in decreased AdoMet levels and the deregulation of signal transduction pathways correlated to methionine metabolism and methionine adenosyltransferase activity [21]. In MCF-7 breast cancer cells, we have demonstrated that AdoMet induces apoptosis and autophagy by the regulation of the expression of miR-34a, miR-34c and miR-486-5p [22].…”
Section: Introductionmentioning
confidence: 92%